Tweeting the Black Travel Experience: Social Media Counternarrative Stories as Innovative Insight on #TravelingWhileBlack. (November 2019) - Dillette, Alana K.; Benjamin, Stefanie; Carpenter, Chelsea
African-Americans in the United States have long since been confronted with harassment and discrimination while traveling because of segregated lodging, restaurants, and other leisure activities. However, African-Americans/Blacks are one of the fastest-growing tourist groups. This work builds on previous research on the Black travel experience analyzing over 300 tweets using the trending hashtag #TravelingWhileBlack through a critical race theory lens. By analyzing how Black tourists are traveling, this study reveals how experiential knowledge of Black travelers can contribute to the learning environment of the tourism industry. Three emergent themes were identified: (1) occurrences of racism, (2) awareness of being Black while traveling, and (3) meaningful experiences traveling while Black, suggesting that experiential knowledge of travelers of color brings different perspectives, which will, it is hoped, move toward eliminating all forms of subordination and create a more just society.